The Role of Collaboration Between Educators and Parents in Creating Effective Learning Administration - Arifin, Ramadhan Zainul; Tumin, Tumin (Jayapangus Press, 2025)
Background this study is based on the fact that the relationship between school and family plays an important role in the educational process, especially in creating a conducive, supportive, and participatory learning environment. Objective this study aims to explore the role of collaboration between educators and parents in creating an effective learning atmosphere, with a focus on its impact on students' learning motivation and academic success. Research Method This study uses a descriptive qualitative approach with a case study method, where data are collected through in-depth interviews, classroom observations, and distributing questionnaires to educators and parents in several elementary and secondary schools. Results The results of the study indicate that collaboration between teachers as seen from three methods, namely through interviews, observations and filling out questionnaires, there are results that most teachers and parents realize healthy collaboration in order to create children's achievements. Forms of effective collaboration include regular open communication, parental involvement in school activities, and consistent moral and academic support at home. Conclusion of the study: good communication between educators and parents can significantly increase students' learning motivation, build self-confidence, and create synergy between home and school in supporting student growth. However, there are challenges that need to be addressed such as differences in perception between teachers and parents, time constraints, and lack of understanding of technology in digital communication. Based on these findings, it is recommended that schools provide communication training and collaborative capacity building for educators and build an integrated communication system with parents.